The importance of logistics distribution centers as nodes in logistics networks - Pavlić Skender, Helga (Array, 2019)
The emergence of logistics distribution centers has in the past few decades become a mass phenomenon that has emerged as a result of global economic processes. As part of logistics networks, logistics distribution centers are the key link between production and the market, i.e. end users, and function as nodes that facilitate international business activities. For this reason, the aim of this paper is to analyze the characteristics of logistics distribution centers on the example of logistics distribution centers of the selected Western and Central European Union countries and examine the prospects for the development of logistics distribution centers in Croatia. The research results indicate that the Republic of Croatia is less competitive in comparison with Western and Central European countries, although it has a number of logistics distribution centers due to insufficient utilization and renewal of transport infrastructure. Logistics distribution centers are an important center of logistics networks, and the countries will have to devote more attention to their development to attract foreign investment and achieve economic development, because their significance will continue to grow in the future.